2004
DOI: 10.1128/jvi.78.3.1324-1332.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Processing and Presentation of Cytotoxic-T-Lymphocyte (CTL) Epitopes Are Major Escape Mechanisms from CTL Immune Pressure in Human Immunodeficiency Virus Type 1 Infection

Abstract: Investigating escape mechanisms of human immunodeficiency virus type 1 (HIV-1) from cytotoxic T lymphocytes (CTLs) is essential for understanding the pathogenesis of HIV-1 infection and developing effective vaccines. To study the processing and presentation of known CTL epitopes, we prepared Epstein-Barr virustransformed B cells that endogenously express the gag gene of six field isolates by adopting an env/nef-deletion HIV-1 vector pseudotyped with vesicular stomatitis virus G protein and then tested them for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 35 publications
4
98
0
Order By: Relevance
“…Recent studies have demonstrated that mutational escape from HIV-specific CTL is caused by interference with the intracellular processing of virus-derived proteins (15,16). We also found HLA-B*35-associated mutations flanking the epitopic regions in Env and Nef.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Recent studies have demonstrated that mutational escape from HIV-specific CTL is caused by interference with the intracellular processing of virus-derived proteins (15,16). We also found HLA-B*35-associated mutations flanking the epitopic regions in Env and Nef.…”
Section: Discussionsupporting
confidence: 49%
“…CTL escape mutations occur at critical sites in the CTL epitopes in the viral genome or in the flanking sequences encoding these epitopes, leading to altered Ag processing (15,16), loss of peptide-HLA binding, or loss of TCR recognition. The two former consequences of these mutations result in the ultimate loss of epitopes to be presented on the surface of virus-infected cells for recognition by CTLs.…”
Section: Irus-specific Cd8mentioning
confidence: 99%
“…A hallmark of HIV infection is its ability to generate immune escape mutations in epitopes (14)(15)(16)(17) and their flanking regions (18,19). CTL escape mutants have been found in population studies, in which they correlate with higher viral loads (20), and they can be transmitted from mother to child (21,22) as well as between sexual partners (ref.…”
mentioning
confidence: 99%
“…N is rarely substituted (1 of 371), and the C-terminal flanking sequences, important for processing (28), are also highly conserved (9,23,29). Only two intraepitopic substitutions that affect processing have been reported by one group (30), suggesting that this may not be a common escape mechanism for SL9. The T cell repertoire for SL9 is broad and sustainable, because large numbers of circulating SL9-T cells are found in 75% of chronically infected patients (10 -12) and can remain elevated for years (17).…”
mentioning
confidence: 99%